A Novel Inflammatory Indicator for Tuberculosis-Associated Obstructive Pulmonary Disease (TOPD): The Systemic Inflammatory Response Index (SIRI) - Hu S; Yu Q; Liu F; Gong F (Dove Medical Press, 2024)
Shengling Hu, Qi Yu, Fenfang Liu, Fengyun Gong Department of Infectious Diseases, Wuhan Jinyintan Hospital, Tongji Medical College of Huazhong University of Science and Technology; Hubei Clinical Research Center for Infectious Diseases; Wuhan Research Center for Communicable Disease Diagnosis and Treatment, Chinese Academy of Medical Sciences; Joint Laboratory of Infectious Diseases and Health, Wuhan Institute of Virology and Wuhan Jinyintan Hospital, Chinese Academy of Sciences, Wuhan, 430023, People's Republic of ChinaCorrespondence: Fengyun Gong, Department of Infectious Diseases, Wuhan Jinyintan Hospital, Tongji Medical College of Huazhong University of Science and Technology; Hubei Clinical Research Center for Infectious Diseases; Wuhan Research Center for Communicable Disease Diagnosis and Treatment, Chinese Academy of Medical Sciences; Joint Laboratory of Infectious Diseases and Health, Wuhan Institute of Virology and Wuhan Jinyintan Hospital, Chinese Academy of Sciences, Wuhan, 430023, People's Republic of China, Email 2020jy0008@hust.edu.cnBackground: The development of chronic obstructive pulmonary disease (COPD) following tuberculosis (TB) is known as tuberculosis-associated obstructive pulmonary disease (TOPD). This study aimed to explore the predictive value of inflammatory indicators for TOPD in TB patients.Methods: Data for this cross-sectional study were collected between January 2014 and January 2022 at Wuhan Jinyintan Hospital. The ratio of inflammatory indicators, including Systemic Inflammatory Response Index (SIRI), C-reactive protein-to-lymphocyte ratio (CLR), eosinophil count-to-lymphocyte count ratio (ELR), were calculated. Univariate and multivariate logistic regression analyses were conducted to explore the association between the ratio of inflammatory indicators and TOPD. Furthermore, the relationship between the ratio of inflammatory indicators and TOPD was investigated using propensity score matching (PSM) and receiver operating characteristic (ROC) curve analysis was performed to evaluate their predictive value for TOPD.Results: The present study included a total of 737 patients, of whom 83 participants (11.26%) had TOPD. Sixty-nine TOPD patients and 69 non-TOPD (NTOPD) patients were successfully matched. Univariate and multivariable logistics regression analysis, conducted before and after PSM, revealed that SIRI was independently significantly associated with an increased risk of TOPD. The area under curve (AUC) of SIRI were 0.702 and 0.668 before and after PSM, respectively. Additionally, patients were stratified into four different groups based on SIRI quartiles for further analysis. The prevalence of TOPD in TB patients showed an increase with higher SIRI values, both before and after PSM.Conclusion: Levels of inflammatory indicators were higher in TOPD patients when compared to NTOPD patients. SIRI may be a simple and useful inflammatory index for assessing TOPD, and TB patients with higher values of SIRI are more likely to be high-risk group for TOPD.Keywords: tuberculosis-associated obstructive pulmonary disease, systemic inflammatory response index, ratio inflammatory indicator, propensity score matching